The Influence of Sufism Thought Shaykh Burhanuddin among the Minangkabau Community in Medan City - Agustianda Agustianda (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2020)
Shaykh Burhanuddin is one of the great famous ulama from West Sumatra, who has developed Islam teachings through the Tariqa Shattariyya which spread until Medan City. Shaykh Burhanuddin developed his thinking through education at the surau. The students who studied at the Surau Shattariyyah opened to learn a whole series of Islamic knowledge. The people of Minangkabau know and practice wisdom. They are not limited to Minangkabau people in West Sumatra. Minangkabau people outside West Sumatra still regard Shaykh Burhanuddin as wali Allah and a great ulama. Shaykh Burhanuddin’s teachings are continuesly developed by his students until they stay in Medan. The purpose of this research was to know the background of sufism thought by Shaykh Burhanuddin, to know the process of the Shaykh Burhanuddin’s sufism thought development into Medan, and to find out why Minangkabau people in Medan follow the teachings of Shaykh Burhanuddin. This research used a descriptive qualitative approach classified to the field research to see how far the development of sufism thought Shaykh Burhanuddin among Minangkabau people in Medan. From this study, it can be concluded that the patterns of thinking influenced the background of Shaykh Burhanuddin’s sufism thought was brought by the previous teacher Ahmad al-Qushashi as well as Shaykh Burhanuddin’s teachers, Shaykh ‘Abd al-Rauf. The idea of Shaykh Burhanuddin sufism is the three main pillars that reconcile shari’a, and sufism developed by his teacher Shaykh ‘Abd al-Rauf, namely the divinity and its relationship with nature, insan al-kamil and the tarekat. In the ideas development of sufism by Shaykh Burhanuddin in Medan city, initially through the Labai and Tuangku from Ulakan, and then due to the increase and spread of Minangkabau community in several districts in Medan. The Minangkabau community in Medan mostly follow the teachings practice of Shaykh Burhanuddin. All forms of the religious pratices are sufism ‘amali activities. Sufism ‘amali is sufism which emphasizes amaliyah (act) such as wirid, dhikr, and other worship.